Secondary prevention: Guidelines of Turkish Society of cerebrovascular diseases 2015 [Ikincil koruma: türk beyin damar hastaliklari dernegi inme tani ve tedavi kilavuzu 2015] - MİDİ, İPEK (Turkish Society of Cerebrovascular Diseases, 2015)
In this section, the brief information about secondary prevention of stroke by the recent developments will be presented. Recommendation regarding the secondary risk factors including hypertension, diabetes, dyslipidemia, atrial fibrillation, symptomatic carotid occlusions, arterial dissections and patent foramen ovale and their treatment approaches will be offered.
Keywords: Atrial fibrillation; Diabetes; Hypertension; Secondary prevention; Stroke